A potential defensive role of TIM-3 on T lymphocytes in the inflammatory involvement of diabetic kidney disease - Chen, Xiao-Jun; Tang, Runyan; Zha, Jie; Zeng, Li; Zhou, Linshan; Liu, Zhiwen; Yang, Danyi; Zeng, Mengru; Zhu, Xuejing; Chen, Anqun; Liu, Hong; Chen, Huihui; et al. (Frontiers in Immunology, 2024)
Objective The aberrant mobilization and activation of various T lymphocyte subpopulations play a pivotal role in the pathogenesis of diabetic kidney disease (DKD), yet the regulatory mechanisms underlying these processes remain poorly understood. Our study is premised on the hypothesis that the dysregulation of immune checkpoint molecules on T lymphocytes disrupts kidney homeostasis, instigates pathological inflammation, and promotes DKD progression. Methods A total of 360 adult patients with DKD were recruited for this study. The expression of immune checkpoint molecules on T lymphocytes was assessed by flow cytometry for peripheral blood and immunofluorescence staining for kidney tissue. Single-cell sequencing (scRNA-seq) data from the kidneys of DKD mouse model were analyzed. Results Patients with DKD exhibited a reduction in the proportion of CD3+TIM-3+ T cells in circulation concurrent with the emergence of significant albuminuria and hematuria (p=0.008 and 0.02, respectively). Conversely, the incidence of infection during DKD progression correlated with an elevation of peripheral CD3+TIM-3+ T cells (p=0.01). Both univariate and multivariate logistic regression analysis revealed a significant inverse relationship between the proportion of peripheral CD3+TIM-3+ T cells and severe interstitial mononuclear infiltration (OR: 0.193, 95%CI: 0.040,0.926, p=0.04). Immunofluorescence assays demonstrated an increase of CD3+, TIM-3+ and CD3+TIM-3+ interstitial mononuclear cells in the kidneys of DKD patients as compared to patients diagnosed with minimal change disease (p=0.03, 0.02 and 0.002, respectively). ScRNA-seq analysis revealed decreased gene expression of TIM3 on T lymphocytes in DKD compared to control. And one of TIM-3's main ligands, Galectin-9 on immune cells showed a decreasing trend in gene expression as kidney damage worsened. Conclusion Our study underscores the potential protective role of TIM-3 on T lymphocytes in attenuating the progression of DKD and suggests that monitoring circulating CD3+TIM3+ T cells may serve as a viable strategy for identifying DKD patients at heightened risk of disease progression.